1994
DOI: 10.1037/0893-164x.8.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Treating obsessive-compulsive disorder among substance abusers: A guide.

Abstract: Recent epidemiological evidence suggests that obsessive-compulsive disorder (OCD) has a lifetime prevalence of 2.5% in the general population, making it the 4th most common psychiatric illness. Some studies indicate that OCD may affect as many as 12% to 13% of substance abusers who seek treatment. Addressing the addiction and a comorbid OCD condition simultaneously may substantially improve treatment prognosis for these dually diagnosed patients. This article explores psychotherapeutic and pharmacologic approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Rates of OCD in substance misusers have generally been found to be low [25], although two studies [9,26] have found rates of 13% and 12% respectively in alcoholic treatment samples. Rates of OCD in substance misusers have generally been found to be low [25], although two studies [9,26] have found rates of 13% and 12% respectively in alcoholic treatment samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rates of OCD in substance misusers have generally been found to be low [25], although two studies [9,26] have found rates of 13% and 12% respectively in alcoholic treatment samples. Rates of OCD in substance misusers have generally been found to be low [25], although two studies [9,26] have found rates of 13% and 12% respectively in alcoholic treatment samples.…”
Section: Resultsmentioning
confidence: 99%
“…The most surprising diagnostic finding was the high rate of OCD, diagnosed in approximately one-fifth of the sample. Rates of OCD in substance misusers have generally been found to be low [25], although two studies [9,26] have found rates of 13% and 12% respectively in alcoholic treatment samples.…”
Section: Discussionmentioning
confidence: 99%
“…The most surprising diagnostic finding was the high rate of OCD, diagnosed in approximately one‐fifth of the sample. Rates of OCD in substance misusers have generally been found to be low [25], although two studies [9,26] have found rates of 13% and 12% respectively in alcoholic treatment samples.…”
Section: Discussionmentioning
confidence: 99%
“…As argued by Fals- Stewart and Lucente (1994), there are two primary reasons to suspect that OCD is often under-detected among substance-abusing populations, making it difficult to evaluate accurately its prevalence among these patients. First, symptoms of OCD are very often overlooked among substance-abusing patients and are often not adequately assessed during intake interviews for treatment entry; counselors and other evaluators in substance abuse treatment programs typically do not have the requisite expertise or experience to recognize co-morbid OCD.…”
Section: Co-morbidity Of Suds and Ocdmentioning
confidence: 99%